Relationship between childhood anemia and intellectual performance in youth - Palacios-Solano, Jesús (2022)
Objective:To determine the relationship between anemia suffered by a generation as children and their performance in the PISA test at 15 years of age. Material and methods:The score that young people in each country obtained in the PISA 2018 test was related to the prevalence of childhood anemia in 2005, the Gross National Income per capita and the Expected Years of Schooling of the Human Development Index of the year 2018. Results:The score obtained in the PISA test is related to anemia as children, the Gross National Income per capita and the Expected Years of Schooling (Educational Effort) with determination coefficients (r2) of 0.5168, 0.1951 and 0.3536, respectively. Conclusion:The score obtained in the PISA test is associated more strongly with the prevalence of anemia that this generation suffered when they were children than with any other current economic or social factor.